Variation in Soil Organic Carbon and Total Nitrogen Stocks under Agricultural Fields and Different Stand Age of Scots pine (Pinus sylvestris L.) - Savacı, Gamze; Sarıyıldız, Temel (Bursa Technical University, 2023)
In this study, the effect of different land use type on the amount of litter, soil organic carbon (TOC) and total nitrogen (TA) stocks in Scots pine (Pinus sylvestris L.) stands and adjacent agricultural lands in the Inebolu district of Kastamonu province of the Black Sea Region were investigated. Samplings were carried out from Scots pine stands of different ages (18- and 30-) and adjacent agricultural lands which were converted from forest land at least 40 year ago. Mineral soil samples were taken from 5 different soil depths (0-5 cm, 5-10 cm, 10-15 cm, 15-20 cm and 20-30 cm) and analysed for pH, bulk density, available phosphorus, available potassium, soil texture, organic matter, organic carbon and total nitrogen contents. Total soil organic carbon and total nitrogen stocks were calculated by multiplying soil depth, bulk density, soil organic carbon and nitrogen contents. The results showed that there were significant differences in soil surface litter, TOC and TN stocks between the Scots pine stands and agricultural lands. In general, the lowest organic carbon stock was found in the 30-year-old Scots pine stand (86.60 t C ha-1), followed by agricultural land (93.70 t C ha-1), and 18-year-old Scots pine stand (115.0 t C ha-1). Similarly, total nitrogen stock was highest in the 18-year-old Scots pine stand (7.86 t N ha-1), while the lowest in the 30-year-old Scots pine stand (5.74 t N ha-1). The amount of litter was the lowest in the agricultural lands. The amount of litter on the forest floor increased with increasing stand age. As a result, it has been shown that different land use types and soil depths can have a significant influence on forest floor litter, soil organic carbon and total nitrogen stocks. So, in future studies, the land use types should also take into account to determine the litter amount, TOC and TN stocks and more detailed studies are in need.

Bu çalışmada, Kastamonu ili İnebolu ilçesinde yayılış gösteren sarıçam (Pinus sylvestris L.) meşcereleri ve bitişiği tarım arazilerinde ölü örtü miktarı, toprak organik karbon (TOK) ve toplam azot (TA) stokları üzerinde farklı arazi kullanım şeklinin etkisi araştırılmıştır. Farklı yaşlardaki sarıçam meşcereleri (18- ve 30-yaş) ile en az 40 yıldır orman arazisinden tarım arazisine dönüştürülmüş alanlardan örnekleme yapılmıştır. Toprak örnekleri 5 farklı toprak derinlik kademesinden alınmış ve toprak örneklerinin pH’ı, hacim ağırlığı, alınabilir fosfor, yarayışlı potasyum, organik madde, toprak tekstürü, TOK ve TA miktarları belirlenmiştir. Toplam TOK ve TA stokları ise toprak derinliği, hacim ağırlığı, karbon ve azot miktarı çarpılarak hesaplanmıştır. Sonuçlar, farklı yaşlarda sarıçam meşcereleri ve tarım arazileri arasında ölü örtü miktarı, TOK ve TA stokları arasında önemli farklılıklar olduğunu göstermiştir. Genel olarak, 30 yaşındaki sarıçam meşceresinde TOK stoku en düşük belirlenirken (86.60 t C ha-1), bunu sırasıyla tarım alanı (93.70 t ha-1), ve 18 yaşındaki sarıçam meşceresi (115.0 t ha-1) takip etmiştir. Benzer şekilde, TA stoku ise en fazla 18 yaşındaki sarıçam meşceresinde (7.86 t ha-1), en düşük 30 yaşındaki sarıçam meşceresinde (5.74 t ha-1) tespit edilmiştir. Tarım arazilerinde ölü miktarı en düşük iken, sarıçam meşcerelerinde yaşa bağlı olarak orman katmanında biriken ölü örtü miktarı artış göstermiştir. Sonuç olarak, ölü örtü miktarı, TOK ve TA stokları üzerinde farklı arazi kullanım durumu ile toprak derinlik kademelerinin önemli derecede etkisi olduğu anlaşılmıştır. Bu nedenle, ölü örtü miktarı, TOK ve TA stokları ile ilgili gelecekteki araştırmalarda arazi kullanım türü de dikkate alınmalı ve daha detaylı çalışmalar yürütülmelidir.
Tarım arazileri ve farklı yaşlardaki sarıçam meşçerelerinde (Pinus sylvestris L.) toprak organik karbon ve azot stoklarının değişimi
KUBAP03/2015-1
Keywords: Forest Industry Engineering; Orman Endüstri Mühendisliği